Construction of retaining wall for the environmental perspective - Adi Saffuan Bin Ahmad (School of Environmental Engineering University Malaysia Perlis, 2011)
This study aimed to identify the type of retaining wall, retaining wall construction method and environmental point of view as well as modification of the panel can be updated to meet the austhetic values. Construction of retaining walls is diiferent in each project. The project is meant Electrified Double Track Project. Constructions of retaining wall at the project site at Jalan Sultanah the Wall Nehemiah Nehemiah wall for which this is the kind of Anchored Wall. Thus, constuction of retaining wall must be in accordance with the view that is environment does not have an adverse impact on the environment .